2015
DOI: 10.1371/journal.pone.0117394
|View full text |Cite
|
Sign up to set email alerts
|

Bioprospecting the American Alligator (Alligator mississippiensis) Host Defense Peptidome

Abstract: Cationic antimicrobial peptides and their therapeutic potential have garnered growing interest because of the proliferation of bacterial resistance. However, the discovery of new antimicrobial peptides from animals has proven challenging due to the limitations associated with conventional biochemical purification and difficulties in predicting active peptides from genomic sequences, if known. As an example, no antimicrobial peptides have been identified from the American alligator, Alligator mississippiensis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
86
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(88 citation statements)
references
References 31 publications
2
86
0
Order By: Relevance
“…A1P was found to have stronger broad-spectrum activity than anticipated from our previous study [8]. Although A1P had weak activity against P. aeruginosa PAO1 (EC 50  = 38.6 μg/ml), it was not effective at concentrations tested against MDR P. aeruginosa (ATCC BAA-2110) (Table 4).…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…A1P was found to have stronger broad-spectrum activity than anticipated from our previous study [8]. Although A1P had weak activity against P. aeruginosa PAO1 (EC 50  = 38.6 μg/ml), it was not effective at concentrations tested against MDR P. aeruginosa (ATCC BAA-2110) (Table 4).…”
Section: Resultsmentioning
confidence: 66%
“…It was also found that A1P had greater activity against S. aureus than P. aeruginosa [8] , indicating it may have stronger activity against Gram-positive organisms.…”
Section: Resultsmentioning
confidence: 99%
“…Apo6 is a naturally occurring (native) peptide identified intact from American alligator blood by de novo peptide mass-spectrometry sequencing [16, 17]. It is the C-terminal sequence of alligator apolipoprotein E, and was discovered using our BioProspector process [16].…”
Section: Resultsmentioning
confidence: 99%
“…Cationic antimicrobial peptides can have broad or specific activity against bacteria, viruses, or fungi and can also have host-directed immuno-modulatory functions [11, 14, 15]. Our group has been working to discover novel antimicrobial peptides from reptiles, including the American alligator ( Alligator mississippiensis ) and the Komodo dragon ( Varanus komodoensis ) [1618]. We have discovered a number of antimicrobial peptides with strong antimicrobial activity against a range of bacteria.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation